Examining the Strategic Role of Soft Skills and Their Implications for Supporting Resource Development: A Narrative Literature Review - Pathan, Pathan; Prayogi, Saiful; Mansur, Mansur; Alaydrus, Kadir Alfan; Faisatullah, Moh (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This narrative literature review examines how soft skills function strategically within human-resource and educational contexts and explores their implications for designing support resources. The review draws on twenty peer-reviewed studies published between 2015 and 2025, selected through systematic screening of keywords such as soft skills, human resources, and educational resources. Through interpretative thematic analysis, the study identifies core competencies of soft skills: communication, collaboration, problem-solving, adaptability, leadership, empathy, time management, creativity, and metacognition. Findings highlight the strategic role of soft skills in recruitment, professional development, team dynamics, and organizational culture within education, as well as systemic implications for curriculum design, assessment practices, teacher preparation, and institutional policy. Major barriers include curricular inertia, limited facilitator capacity, measurement challenges, and equity gaps in learner engagement. The review recommends embedding explicit soft skills into educational program frameworks and investing in sustained educator training. Future research should undertake detailed, longitudinal analyses of student soft-skills development using robust quantitative measures alongside qualitative approaches to identify effective instructional strategies and contextual factors that drive sustainable skill acquisition.